The Influence of Leadership Style and Motivation on Employee Performance at Four Points By Sheraton Bali, Kuta - Gusti Ayu Kadek Putri Diantari; Irene Hanna H. Sihombing; Ida Ayu Kalpikawati (STIE Pariwisata API Yogyakarta, 2024)
The aim of this research is to determine the influence of leadership style and work motivation on employee performance. The population in the research were employees of Four Points by Sheraton Bali, Kuta with a sample of 75 respondents. The data analysis techniques used in this research are Multiple Linear Regression, t Test, F Test, Correlation Coefficient and Determination. Based on the research results, it can be seen that leadership style has a positive and significant effect on employee performance, work motivation has a significant positive effect on employee performance and leadership style and work motivation simultaneously have a significant effect on employee performance. The magnitude of the influence of leadership style and work motivation variables on employee performance is 75.5%. The advice that can be given by researchers is that it is hoped that the leaders of Four Points by Sheraton Bali, Kuta will always evaluate the results of employee work, and provide rewards when employees can complete work that exceeds the standards that have been set, give praise when employees are able to complete work well and always supervise employees when working.